2011
DOI: 10.1056/nejmsa1103216
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhoods, Obesity, and Diabetes — A Randomized Social Experiment

Abstract: BACKGROUND The question of whether neighborhood environment contributes directly to the development of obesity and diabetes remains unresolved. The study reported on here uses data from a social experiment to assess the association of randomly assigned variation in neighborhood conditions with obesity and diabetes. METHODS From 1994 through 1998, the Department of Housing and Urban Development (HUD) randomly assigned 4498 women with children living in public housing in high-poverty urban census tracts (in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
617
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 819 publications
(679 citation statements)
references
References 23 publications
24
617
2
6
Order By: Relevance
“…However, in the only study of its kind, Ludwig and colleagues 109 analyzed data from the Moving to Opportunity Study, in which 4498 women from 5 cities in the United States were randomized to 1 of 3 conditions: a voucher to move to a low-poverty neighborhood, a voucher to move to any neighborhood, or no voucher (control group). After 10 to 15 years of follow-up, women receiving the low-poverty voucher were significantly less likely to have a BMI >35 kg/m 2 , a BMI >40 kg/m 2 , or a glycated hemoglobin >6.5% compared with women in the control group.…”
Section: Residential Environmentsmentioning
confidence: 99%
“…However, in the only study of its kind, Ludwig and colleagues 109 analyzed data from the Moving to Opportunity Study, in which 4498 women from 5 cities in the United States were randomized to 1 of 3 conditions: a voucher to move to a low-poverty neighborhood, a voucher to move to any neighborhood, or no voucher (control group). After 10 to 15 years of follow-up, women receiving the low-poverty voucher were significantly less likely to have a BMI >35 kg/m 2 , a BMI >40 kg/m 2 , or a glycated hemoglobin >6.5% compared with women in the control group.…”
Section: Residential Environmentsmentioning
confidence: 99%
“…Recently, an important 10-15 years long-term study demonstrated that moving patients from low income neighborhoods to higher ones improved their obesity and diabetes (Ludwig et al, 2011;2012). In this study examined three SEFs: i) whether the patients lived in a rural as opposed to urban counties; ii) whether the patients lived in a county with a family income equal or lower than $50000 per year as opposed to a higher one; and iii) whether the patients lived in a low college education attainment county were examined.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a recent social experiment in which low-income families were randomized to receive vouchers that moved them to healthier neighborhoods found reduced prevalence of obesity and diabetes after 5 years. 33 Such studies are rare, however, and are a reminder of the difficulty of demonstrating impact of policy approaches and the need for a broader spectrum of research to guide policies. 34 …”
Section: Tiered Approach To Preventionmentioning
confidence: 99%